Social Stratification and Inequality of Access to Public Services in the Cities of Surabaya, Malang, and Sidoarjo: A Marxian and Weberian Conflictual Study - Silvia Eka Nur Wulandari; Sugeng Harianto (Dinasti Publisher, 2025)
This study aims to explore in detail the structural mechanisms that reinforce inequality, focusing on the interaction between economic (class), social status (prestige) and power (authority) dimensions and analyzing how social stratification produces and reproduces inequality in access to public services in Surabaya City, Malang City and Sidoarjo Regency using a conflictual approach based on Marxian and Weberian theories. The study adopted a qualitative method with a multicluster case study design, combining in-depth interview techniques, participatory observation and documentation analysis. The research shows that inequality in access to education, health and public administration services is significantly influenced by unequal structures of social class, status and power. In the Marxian perspective, such inequality is a reflection of the dominance of the capitalist class in accessing and controlling public resources, while the Weberian approach reveals that social status and bureaucracy create systematic differentiation of opportunities. This study makes a theoretical contribution by synergizing two classic approaches in explaining the phenomenon of urban social inequality in Indonesia and filling the void in stratification studies that have tended to be descriptive. Practically, the results of this study recommend the need to reform the public service system based on the principles of distributive justice and equal access. The findings also imply that without substantial structural changes, inequality in public services will continue to reproduce the cycle of social injustice in urban spaces.